Part 1: Monitoring training status with player-tracking technology. Still on the road to Rome - Traditional practices and new concepts - Lacome, M.; Simpson, B. M.; Buchheit, M. (ASPETAR Sports Medicine Journal, 2018)
The last 15 years have seen an incredibly rapid development of (micro)technology in the field4. Player tracking has become one of the most important components of load monitoring in team sports5. Most professional teams use GPS or alternative tracking systems on a regular basis (e.g. Prozone®, TRACAB®, Inmotio®). Training load reports are now generated within moments following each training session and have become a key element in programming both team and individual training sessions.